Trails of Performance: A Study of Real Time Optimization Techniques in Heterogeneous Natural Environments for VR - Cruz, Lucas Rangel da; Santos, Nicole Cristina Vieira dos; Souza, Luiz André de; Oliveira, Andressa dos Santos; Silva, Marcelo Arêas Rodrigues da; Santos, Joel André Ferreira dos (Anais do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames), 2025)
Introduction: Virtual reality has gained widespread adoption across training, education, and other fields, yet hardware limitations, especially in lower-end standalone devices, pose challenges for accessibility and quality. Moreover, optimization is still a slow and experimental process, often at odds with the fast pace of research, especially for small teams. Thus, effective software optimization is critical for delivering a smooth and enjoyable experience for users and developers. Objectives: This study evaluates various optimization techniques and proposes a hybrid approach to address limitations observed in a target VR scene. Methodology: Performance metrics were collected on a VR device at key points in a test scene for each technique. Results were compared to identify the most effective methods, which were then combined into a hybrid technique and further assessed. Results: The hybrid technique increased performance by 26%, achieving an average frame time reduction of around 8 ms compared to individual techniques, with the second-best technique, a Level of Detail system, yielding a reduction of around 4 ms on average. However, the hybrid technique’s broader applicability outside the test scene requires further experimentation.